How Feasible are Jack Ma's Proposals for Computerized Planning?. (1st October 2019) - Cockshott, Paul
Abstract : The use of linear optimization for the construction of economic plans was first introduced by Kantorovich with an algorithm similar to those later developed in the West by Danzig. In recent years linear optimization packages have become readily available on desktop computers, an example being the lp-solve system. In this paper I first show how the lp-solve package can be used to construct macro-economic plans starting from information in IO table. I then examine the empirical computational complexity of the package in dealing with this sort of problem. This will show that the complexity is too great to allow the package to be applied to highly disaggregated IO tables. As an alternative to lp-solve I explain the Harmony algorithm and how that can be extended to the problem of multi-year plans. Performance measurements are given which indicated that the Harmony algorithm has a markedly lower computational complexity than lp-solve, making it more suitable for highly disaggregated plans.